Op soek na diepgang in prediking : Die bydrae van die literêre geskiedenis van die Bybel - Jonker, Louis (Stellenbosch Theological Journal, 2019)
Preaching the Old Testament: Why the literary history matters It is generally accepted that the genre of an Old Testament text (or, for that matter, of any biblical text) should be taken into consideration when planning a sermon on such a text. The literary form should be respected in the re-communication of the contents of a text. An aspect which is often neglected in preaching, however, is not literary form, but literary history. Why would it be important to pay attention to the formation processes which brought about the final form of the particular Old Testament text? Does it bring any further value for sermon-making when the history of growth of a text is taken into consideration? This contribution will be a plea for involving the literary history of Old Testament texts into the process of preaching. It will emphasise that this historical aspect could enrich the hermeneutical processes that are inevitable for preparing a sermon.